A systematic approach to identify the critical factors of Taiwan International Logistics: a grey relational approach. (2017) - Lee, Tzong-Ru; Law, Kris M.Y.; Huang, Dan-Ching; Pan, Meng-Juan
Globalisation of trade caused an increase in competition and forced Taiwan to expand its logistical operation beyond the Asia-Pacific. In order to be able to improve its logistical operation, Taiwan needs to know its current competence level compared to its neighbouring nations. In an attempt to justify the performance of Taiwan International Logistics (TIL), World Bank's logistics performance index was first used to identify TILs current competence. Grey relation analysis was then used to analyse TIL with reference to its infrastructure and timeliness. Six critical factors were obtained and these factors were used to identify TILs current problems as well as offer direction for future advancement.